The Effect of a Cardiovascular Polypill Strategy on Pill Burden. Issue 6 (December 2015) - Truelove, Michael; Patel, Anushka; Bompoint, Severine; Brown, Alex; Cass, Alan; Hillis, Graham S.; Peiris, David; Rafter, Natasha; Reid, Christopher M.; Rodgers, Anthony; Tonkin, Andrew; Usherwood, Tim; et al.
Summary: Aims: Recent trials of cardiovascular polypills in high‐risk populations show improvements in the use of cardiovascular preventive treatments, compared to usual care. We describe patterns of pill burden in Australian practice, define the impact of polypill therapy on pill burden, and explore how physicians add medication to polypill therapy. Methods: The Kanyini Guidelines Adherence with the Polypill Study was an open‐label trial involving 623 participants in Australia which randomized participants to a polypill strategy (containing a statin, antiplatelet agent, and two blood‐pressure‐lowering medications) or usual care. Participants either had established cardiovascular disease or were at high calculated risk (≥15% over 5 years). Current medications, daily pill burden, and self‐reported use of combination treatment were recorded prior to randomization and at study end. Median pill burden at baseline and study end was compared in both arms. Subgroup analysis of the polypill strategy on trial primary outcomes was conducted by pill burden at baseline. Results: Median total and cardiovascular pill burdens of the polypill group decreased from 7 to 5 and from 4 to 2, respectively (median change −2; IQR −3, 0), with no change in the usual care group (comparison of change; P  <   0.001). No change was seen for noncardiovascular medications. Of those still using the polypill at study end, 43.8% were prescribed additional medications; 84.5% of these additional medications were blood‐pressure‐lowering medications. Within the polypill group, lower pill burden at baseline was associated with greater increases in the use of indicated cardiovascular preventive medications at study end compared to those with higher pill burdens. No trend was observed between the level of baseline pill burden and the effect of poylpill treatment on systolic blood pressure or total cholesterol. Conclusion: A cardiovascular polypill in contemporary Australian practice reduces cardiovascular and total pill burdens, despite frequent prescription of additional medications.